HUNSTON, SUSAN y THOMPSON, GEOFF (Eds.). (2001). Evaluaron in Text: Authorial Stance and the Construction ofDiscourse. Oxford: Oxford University Press. 225 pp. ISBN 0-19-829986-9 - Kaplan, Nora (Revista Latinoamericana de Estudios del Discurso, 2021)
HUNSTON, SUSAN y THOMPSON, GEOFF (Eds.). (2001). Evaluaron in Text: Authorial Stance and the Construction ofDiscourse. Oxford: Oxford University Press. 225 pp. ISBN 0-19-829986-9.